Faradaic Electrodes Open a New Era for Capacitive Deionization. Issue 22 (11th October 2020) - Li, Qian; Zheng, Yun; Xiao, Dengji; Or, Tyler; Gao, Rui; Li, Zhaoqiang; Feng, Ming; Shui, Lingling; Zhou, Guofu; Wang, Xin; Chen, Zhongwei
Abstract: Capacitive deionization (CDI) is an emerging desalination technology for effective removal of ionic species from aqueous solutions. Compared to conventional CDI, which is based on carbon electrodes and struggles with high salinity streams due to a limited salt removal capacity by ion electrosorption and excessive co‐ion expulsion, the emerging Faradaic electrodes provide unique opportunities to upgrade the CDI performance, i.e., achieving much higher salt removal capacities and energy‐efficient desalination for high salinity streams, due to the Faradaic reaction for ion capture. This article presents a comprehensive overview on the current developments of Faradaic electrode materials for CDI. Here, the fundamentals of Faradaic electrode‐based CDI are first introduced in detail, including novel CDI cell architectures, key CDI performance metrics, ion capture mechanisms, and the design principles of Faradaic electrode materials. Three main categories of Faradaic electrode materials are summarized and discussed regarding their crystal structure, physicochemical characteristics, and desalination performance. In particular, the ion capture mechanisms in Faradaic electrode materials are highlighted to obtain a better understanding of the CDI process. Moreover, novel tailored applications, including selective ion removal and contaminant removal, are specifically introduced. Finally, the remaining challenges and research directions are also outlined to provide guidelines for future research. Abstract : Faradaic electrodes open a new era for capacitive deionization (CDI) by providing enhanced salt removal capacity and energy‐efficient desalination for high salinity streams. Advances in the development of Faradaic electrodes for CDI are comprehensively summarized, spanning from cell architectures, key performance metrics, advanced materials, and related ion capture mechanisms, to tailored applications as well as main challenges and perspectives.